Public Sphere in Hybrid Media Systems in Central and Eastern Europe - Peruško, Zrinjka (Javnost-The Public, 2021)
The article explores the concept of hybridity in relation to political and media-related change and its implications for the contemporary public sphere in Central and Eastern Europe. Two key approaches to hybridity are contrasted and examined to this end: the well-established concept of the hybrid media system, defined in terms of a combination of older and newer media logics in platform societies in the times of late modernity, is contrasted with the concept of hybridity in political and media systems in relation to unsuccessful regime change and democratization or recent illiberal backsliding. Hybridity as the outcome of longue durée contextual conditions, as well as the more recent mediatization, is present also in the contemporary public spheres in CEE countries in relation to specific conditions and contingencies of individual mediascapes.